2001
DOI: 10.1021/jm010841w
|View full text |Cite
|
Sign up to set email alerts
|

4‘-Arylpyrrolomorphinans:  Effect of a Pyrrolo-N-benzyl Substituent in Enhancing δ-Opioid Antagonist Activity

Abstract: A new method for the preparation of N-benzylpyrrolomorphinans has been developed. Thus Michael reaction of the benzylimines of oxycodones and oxymorphones with nitrostyrenes gave a series of 4'-aryl-N-benzylpyrrolomorphinans. These were selective delta antagonists of much higher in vitro potency (with 5a having K(e) delta = <1 nM) than their binding affinities predicted. In mice in vivo assays 5a showed good delta antagonist activity in the anti-writhing analgesic assay and also inhibited delta agonist-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Among a limited number of such pyrrolomorphinans synthesized and evaluated, it was found that compound 16 possessing a 4-methylphenyl substituent on the pyrrole ring displayed ␦ antagonist activity with a K e of 14.1 nM and partial agonist activity with and EC 50 of 1360 nM and E max of 34% in [ 35 S]GTP ␥ S binding assays in CHO cells expressing human ␦ and opioid receptors. 63 Portoghese and coworkers have, for a long time, pursued the design of bivalent ligands to probe opioid receptor complexes. [64][65][66][67] The recent demonstration of the existence of -␦ receptor hetero-oligomeric complexes has spurred further interest in the design of such bivalent ligands that could potentially interact with these receptor complexes.…”
Section: E122mentioning
confidence: 99%
“…Among a limited number of such pyrrolomorphinans synthesized and evaluated, it was found that compound 16 possessing a 4-methylphenyl substituent on the pyrrole ring displayed ␦ antagonist activity with a K e of 14.1 nM and partial agonist activity with and EC 50 of 1360 nM and E max of 34% in [ 35 S]GTP ␥ S binding assays in CHO cells expressing human ␦ and opioid receptors. 63 Portoghese and coworkers have, for a long time, pursued the design of bivalent ligands to probe opioid receptor complexes. [64][65][66][67] The recent demonstration of the existence of -␦ receptor hetero-oligomeric complexes has spurred further interest in the design of such bivalent ligands that could potentially interact with these receptor complexes.…”
Section: E122mentioning
confidence: 99%
“…DOPr antagonist potency and selectivity was restored in 6a by pyrrole-ring substitution in the 4′ and 5′-positions as in 6b , 13 with further enhancement of DOPr potency by introduction of a 1′(N)-benzyl substituent as in 3a . 5 The herein reported example ( 4b ) is a non-selective opioid antagonist which is best compared with 6b since a side chain CO 2 Et is regarded as an isostere of a phenyl group 14 so that the 4′-benzyl group of 6b is comparable to the 4′-CH 2 CO 2 Et group of 4b . Despite the structural differences between 6b and 4b in the 1′-(N) and 5′-positions (substituents R 1 and R 3 in structure 6 ) they have comparable DOPr antagonist potency (Ke 6b 2.1nM, 4b 6.8nM) but equally high MOPr (6.6 nM) and KOPr (4.3 nM) antagonist potencies of 4b means DOPr antagonist selectivity in 4b is lost whereas 6b was 50-fold selective over both MOPr and KOPr.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the structural differences between 6b and 4b in the 1′-(N) and 5′-positions (substituents R 1 and R 3 in structure 6 ) they have comparable DOPr antagonist potency (Ke 6b 2.1nM, 4b 6.8nM) but equally high MOPr (6.6 nM) and KOPr (4.3 nM) antagonist potencies of 4b means DOPr antagonist selectivity in 4b is lost whereas 6b was 50-fold selective over both MOPr and KOPr. 13 Since it was established that the 1′-(N)-benzyl group had a positive effect particularly on DOPr antagonist potency, 5 it appears that the 5′-hydroxyl group has the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations